Biological Efficacy of Essential Oils and Plant Extracts of Cultivated and Wild Ecotypes of Origanum vulgare L. (7th April 2020) - Jan, Sumira; Rashid, Megna; Abd_Allah, Elsayed F.; Ahmad, Parvaiz
Abstract : Current study describes discrepancy in biological efficacy of methanolic and ethanolic extracts and essential oil procured from cultivated and wild accessions of Origanum vulgare. Simultaneously, quantification of carvacrol, thymol, caryophyllene, ocimene, and terpinen-4-ol contents was determined via GC-MS and GC in both accessions. The results revealed significantly a higher antioxidant potential by methanolic extracts displaying IC50 of 19.9  μ g/ml compared to essential oil with IC50 of 10  μ g/ml, and ethanolic extracts were found to be less effective even at the concentration of 3  μ g/ml. However, essential oil from wild and cultivated accessions of O. vulgare exhibited significantly high antimicrobial activity against all 39 bacteria, 16 fungi, and 2 yeast species tested due to higher concentrations of carvacrol and thymol as revealed by GC analysis. Inhibition of tyrosinase activity in a C6 cell line displayed 81.0%–87.0% depigmentation potential of the methanolic extracts, while ethanolic extracts revealed a maximum of 88.54–99.02% inhibition of reactive oxygen species (ROS) in H2 O2 -treated cells. Hence, the study determines efficacy of essential oil against microbial pathogenesis, methanolic extracts as potent depigmentation agents, and ethanolic extracts as potent free radical scavenger.